13th Annual Meeting of the Safety Pharmacology Society: focus on novel technologies and safety pharmacology frontiers. (September 2014) - Cavero, Icilio
<x xml:space="preserve">Abstract</x> Introduction: The 13th Annual Meeting of the Safety Pharmacology (SP) Society discussed novel therapeutic areas, recent regulatory developments, emerging biology technologies and non-pharmaceutical dairy products that may need SP evaluations for ensuring their human safety. Areas covered: The meeting honored Willem Einthoven, the father of electrocardiography. The Comprehensive in vitro Proarrhythmia Assay (CiPA) is an under-discussion proposal for replacing the International Conference on Hamonization (ICH) S7B guideline strategy. Drugs targeting epigenetic mechanisms (e.g., histone deacetylase inhibitors) have the potential to produce proarrhythmic safety liabilities by dysregulating the synthesis of cardiac ion channel proteins as well as the intracellular machinery, moving them to sarcolemmal residence. Novel frontiers of regulatory SP investigations are functional food and probiotic (microorganisms) preparations. Expert opinion: The CiPA initiative is a unique opportunity for concerned stakeholders to drive SP into the adoption of 21st century safety assessment platforms, which, for discovering and mitigating mechanisms conferring safety risks to drugs, apply chiefly in silico and in vitro rather than traditional in vivo pharmacodynamics assays. The SP evaluation of functional foods and probiotics needs the development of product-tailored investigational approaches.